Self-efficacy and stress as determinants of test anxiety among selected secondary school students - Ogunola, Abiodun Adekunle; Odumesi, Kehinde Rebecca (Journal of Indonesian Psychological Science (JIPS), 2025)
This study examined the roles of self-efficacy and stress in influencing test anxiety among students from selected secondary schools in Ijebu-Ode, Ogun State, Nigeria. Specifically, it explored how students’ beliefs in their academic abilities and the stress they experience during their academic journey contribute to anxiety before, during, and after assessments. A descriptive survey design was adopted, involving 250 students from eight schools. Data were collected using three standardized instruments: the Revised Test Anxiety Scale (RTA), the Rosenberg Self-Esteem Scale (RSES), and the Standard Stress Scale (SSS). Regression analysis revealed that self-efficacy significantly predicted test anxiety (β = 0.956, t = 51.43, p .05), as did stress (β = 0.252, t = 4.10, p .05). The joint analysis showed that self-efficacy (β = 1.834, t = 49.55, p .05) and stress (β = -0.009, t = 0.015, p .05) together accounted for 91.4% of the variance in test anxiety. These findings highlight the complex psychological interplay, suggesting that while self-efficacy is generally protective, in certain high-pressure contexts it may paradoxically relate to higher anxiety. The study recommends that teachers and parents foster students’ self-efficacy by promoting realistic goal-setting, providing constructive feedback, and reinforcing their strengths.KEY WORDS: self-efficacy; stress; test anxiety; secondary school students; academic pressure